Social Media Managers’ and Journalists’ Role in Maintaining Local Wisdom in A Mediatized Rural Area - Yudha, Reza Praditya; Hendriyani, Hendriyani (Jurnal The Messenger, 2022)
Introduction: This study explores on how social media managers and journalists in Tulungagung narrating ‘Aksi 212’ (Action 212) protests. Social media managers and journalists are the actors who have an active role in producing, constructing and sharing information. The solidarity protests and the news about ‘Aksi 212’ had appeared in various media and regions in conflicting narratives. However, there was no news nor any solidarity protest occurred in Tulungagung.Methods: This study applies digital ethnography to examine five media that keep updating their posts and interview six journalists and media managers who have a large number of followers in Tulungagung.Findings: The social media managers and journalists avoid any information that may bring a potential conflict, eventhough it becomes a national issue. On the date of the ‘Aksi 212’, the @radar_tulungagung and @hits_tulungagung accounts did not share any posts. Meanwhile, the @jtv_tulungagung, @kacamata_tulungagung and @tulungagung_sparkling uploaded local news. The social media managers and journalists provide information in accordance with the local wisdom--the harmony and togetherness--as they realize the legal and social consequences.Originality: The previous mediatization studies focus on the role of the media as institutions and examine the ‘Aksi 212’ in the context of political conflict. This study examines the ‘Aksi 212’ by using the socio-constructivist approach to understand the mediatization from the perspective of the rural society, that upholds the local wisdom in their media engagement and observes the society’s practice in utilizing media.